2021
DOI: 10.1007/s00066-021-01855-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between treatment-related lymphopenia and survival in glioblastoma patients following postoperative chemoradiotherapy

Abstract: Purpose Our study investigated the association between treatment-related lymphopenia and overall survival (OS) in a series of glioblastoma (GBM) patients. We also explored clinical and dosimetric predictors of lymphocytes depletion. Methods Between 2015 and 2019, 64 patients were treated at the same institution with postoperative chemoradiotherapy. Peripheral lymphocyte count (PLC) data and dose–volume histogram parameters were collected. Radiotherapy (RT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Especially in combination with systemic chemotherapy like 5‑FU [ 50 ] or the PCV scheme [ 51 ], the use of iv radiosensitization with halogenated pyrimidines caused increased amounts of grade III and IV toxicity, last-mentioned in a large phase III trial (RTOG 9404) on patients with anaplastic astrocytoma in 2004, which also concluded a lack of survival benefit [ 52 ]. With emerging relevance of combination treatment of RT and temozolomide or nitrosoureas (both also having accompanying potential for myelosuppression and lymphopenia, a side effect with unclear relevance concerning treatment outcome [ 53 ]), the use of halogenated pyrimidines as radiosensitizers for glioma treatment did not prove to be profitable enough and was abandoned. Table 7 summarizes the published trials evaluating halogenated pyrimidines as radiosensitizers.…”
Section: Resultsmentioning
confidence: 99%
“…Especially in combination with systemic chemotherapy like 5‑FU [ 50 ] or the PCV scheme [ 51 ], the use of iv radiosensitization with halogenated pyrimidines caused increased amounts of grade III and IV toxicity, last-mentioned in a large phase III trial (RTOG 9404) on patients with anaplastic astrocytoma in 2004, which also concluded a lack of survival benefit [ 52 ]. With emerging relevance of combination treatment of RT and temozolomide or nitrosoureas (both also having accompanying potential for myelosuppression and lymphopenia, a side effect with unclear relevance concerning treatment outcome [ 53 ]), the use of halogenated pyrimidines as radiosensitizers for glioma treatment did not prove to be profitable enough and was abandoned. Table 7 summarizes the published trials evaluating halogenated pyrimidines as radiosensitizers.…”
Section: Resultsmentioning
confidence: 99%
“…This may partially explain the T cell lymphopenia in glioblastoma patients. However, treatment (radiation and TMZ) associated T cell lymphopenia was also very common [ 83 , 84 ] .…”
Section: Drug Resistance To Immunotherapy In Glioblastomamentioning
confidence: 99%